Passivo ambiental de nutrientes e matéria orgânica na agricultura empresarial de Mato Grosso - GOMES, Vallência Maíra (Universidade Federal do Pará, 2018)
The intensive exploitation of soils of Mato Grosso-Brazil savanna, associated with inadequate farming techniques has taken to an increasing and noticeable soil degradation. As a result, grows among the large farmers of Mato Grosso the adoption of the no-tillage system. The environmental chemistry and agronomy allied to ecological economics and environmental management provide the interdisciplinary basis of this study, which aims to estimate the environmental liability of nutrients and organic matter of the soil in the mato-grossense savanna from the perspective of the economic viability of different soil management systems. After the identification of areas in which the environmental costs were or were not incorporated, was made the economic-financial feasibility analysis, considering the different types of management. The results point to a segmented reduction of environmental liabilities in areas where no-till farm system is adopted. However, in the short term, higher profitabilities is still combined with less sustainable traditional management techniques. However, other externalities are still associated of the no-tillage not addressed in this study, such as more intensive use of herbicides and insecticides, which may compromise its environmental results.